Human leukaemic cell lines synthesize hyaluronan to avoid senescence and resist chemotherapy - Lompardía, Silvina Laura (2013)
Hyaluronan (HA) is one of the major components of the extracellular matrix. Several solid tumors produce high levels of HA, which promotes survival and multidrug resistance (MDR). HA oligomers (oHAs) can block HA effects. However, little is known about the role of HA in hematological malignancies. The aim of this work was to determine whether HA or its oligomers can modulate the proliferation of leukemia cells as well as their effect on MDR. Receptors and signaling pathways involved were also analyzed. For this purpose, the human leukemic cell lines K562 and Kv562, which are sensitive and resistant to Vincristine (VCR), respectively, were used. We demonstrated that HA induced cell proliferation in both cell lines. On K562 cells, this effect was mediated by cluster differentiation 44 (CD44) and activation of both phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) and mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) pathways, whereas on Kv562 cells, the effect was mediated by receptor for hyaluronan-mediated motility (RHAMM) and PI3K/Akt activation. The inhibition of HA synthesis by 4-methylumbelliferone (4MU) decreased cell line proliferation and sensitized Kv562 to the effect of VCR through P-glycoprotein (Pgp) inhibition, in both cases with senescence induction. Moreover, oHAs inhibited K562 proliferation mediated by CD44 as well as Akt and ERK down-regulation. Furthermore, oHAs sensitized Kv562 cells to VCR by Pgp inhibition inducing senescence. We postulate that the synthesis of HA would promote leukemia progression mediated by the triggering of the above-mentioned proliferative signals. These findings highlight the potential use of oHAs and 4MU as coadjuvant for drug-resistant leukemia.